2015
DOI: 10.1186/s12978-015-0001-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between wanting circumcision and risky sexual behaviour in Zimbabwe: evidence from the 2010–11 Zimbabwe demographic and health survey

Abstract: BackgroundZimbabwe adopted voluntary medical male circumcision (VMMC) as an additional HIV prevention strategy in 2009. A number of studies have been conducted to understand the determinants of VMMC uptake but few studies have examined the characteristics of men who are willing to get circumcised or the link between wanting circumcision and risky sexual behaviour. This study investigated the relationship between wanting male circumcision and engaging in risky sex behaviours. This was based on the assumption th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
3
12
0
Order By: Relevance
“…The findings in this study indicate that the willingness to be circumcised was higher among those that had engaged in more risky behaviours. In other recent cross sectional studies conducted in 2010/ 2011 in Zimbabwe [ 24 ] and 2008 in Botswana [ 25 ], willingness to be circumcised was also associated with more risky sexual behaviours such as having multiple sexual partners [ 24 , 25 ], non-marital partners, and having engaged in transactional sex [ 24 ]. Even those who had used a condom at last non-marital sex were more willing than those who had not had non-marital sex in the preceding year, which could indicate that they did not think condoms gave full protection or that they had not used condoms consistently at all higher risk sexual encounters.…”
Section: Discussionmentioning
confidence: 99%
“…The findings in this study indicate that the willingness to be circumcised was higher among those that had engaged in more risky behaviours. In other recent cross sectional studies conducted in 2010/ 2011 in Zimbabwe [ 24 ] and 2008 in Botswana [ 25 ], willingness to be circumcised was also associated with more risky sexual behaviours such as having multiple sexual partners [ 24 , 25 ], non-marital partners, and having engaged in transactional sex [ 24 ]. Even those who had used a condom at last non-marital sex were more willing than those who had not had non-marital sex in the preceding year, which could indicate that they did not think condoms gave full protection or that they had not used condoms consistently at all higher risk sexual encounters.…”
Section: Discussionmentioning
confidence: 99%
“…These finding supports the idea that undergoing VMMC is likely to encourage participants to engage in risky sexual acts. Results from a study done in Zimbabwe showed a strong association between willingness to be circumcised in participants that had risky sexual practices (multiple partners, being involved in transactional sex and non-condom use) [25]. This observation may explain the continued risky sexual practices in circumcised participants as being carried forward following circumcision and likely due to the perceived protective effect.…”
Section: Discussionmentioning
confidence: 98%
“…This is one of the risky sexual practices following VMMC, which may be as a result of the misunderstanding of the protective effect of VMMC [24]. Furthermore, the desire to be circumcised was associated with knowledge of the perceived protective effect of VMMC among the uncircumcised individuals who were practicing risky sexual behaviours as well as high incidence of STIs in circumcised clients [21,25]. In this case, the motivation to get circumcised could be associated with the desire to freely engage in risky sexual practices due to the perceived protective effect of VMMC.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in a comparative study, risky sexual practices were observed less in the uncircumcised clients who showed interest to be circumcised than in the circumcised ones [34]. Results from a study done in Zimbabwe showed a strong association between willingness to be circumcised in clients that had risky sexual practices (multiple partners, being involved in paid sex and non-condom use) [26]. This observation may explain the continued risky sexual practices in circumcised clients as being carried forward following circumcision and likely due to the perceived protective effect.…”
Section: Discussionmentioning
confidence: 99%
“…This is one of the risky sexual practices following VMMC, which may be as a result of the understanding of the protective effect of VMMC [25]. Furthermore, the desire to be circumcised was associated with knowledge of the perceived protective effect of VMMC among the uncircumcised individuals who were practicing risky sexual behaviour [26]. In this case, the motivation to get circumcised could be associated with the desire to freely engage in risky sexual practices due to the perceived protective effect of VMMC.…”
mentioning
confidence: 97%